2012
DOI: 10.1103/physrevb.85.045325
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced shot noise in asymmetric interacting two-level systems

Abstract: We study a model of two interacting levels that are attached to two electronic leads, where one of the levels is attached very weakly to the leads. We use rate equations to calculate the average current and the noise of electrons transmitted through the two levels. We show that the shot noise is enhanced because of the interactions and that the Fano factor depends on the properties of the couplings between the levels and the leads. We study both sequential tunneling and cotunneling processes and show that ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…As derived in Ref. [13], the Fano factor of the super-Poissonian noise in a telegraphic system is described by the expression…”
Section: Numerical Simulationsmentioning
confidence: 98%
See 1 more Smart Citation
“…As derived in Ref. [13], the Fano factor of the super-Poissonian noise in a telegraphic system is described by the expression…”
Section: Numerical Simulationsmentioning
confidence: 98%
“…Theory has shown that in single-level QDs the Pauli exclusion principle and the repulsive Coulomb interaction result in anti-bunching [7][8][9][10]. However, occupation dynamics in multi-level QDs can give rise to bunching, and correspondingly, super-Poissonian noise [11][12][13]. The electron transport in an interacting two-level system is a telegraphic process if the tunnel couplings of one level are much stronger than of the other [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the presence of localized states in a conductor will give rise to super-Poissionian noise, depending on the ratio of traversal and localized time scales of the current carrying electrons [33]. The latter applies to conductors having twolevel fluctuators [34]. Hence, for the purpose of simplifying the analysis we will restrict noise spectroscopy to junctions having neither VITLS signatures nor Kondo-like zero-bias anomalies in the differential conductance, but that only show molecular signatures as step-down or step-up features.…”
Section: B Experimental Observationsmentioning
confidence: 99%
“…Alternatively, one could repeatedly measure the time τ it takes for the number of measured quantum jumps to reach n and construct a probability density distribution P (τ (n)), as we demonstrate in Fig.(1). The first quantity, n(t), is an example of a fixed-time statistic [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], while τ (n) is an example of a fluctuating-time statistic [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Considering the important role time-dependent fluctuations have, analysis of quantum fluctuations has therefore been focused on calculating either fixed-time and fluctuating-time statistics, and exploring the relationship between the two [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%